Digital marketing management : a handbook for the current (or future) CEO - Zahay, Debra L. (Digital and social media marketing and advertising collection., 2015)
This book is for managers and would-be managers who need to upgrade their knowledge of digital marketing. Told from the perspective of marketing strategy, it puts digital marketing in the context of firm strategy selection. The first step in digital marketing is to understand your company and your brand. The next step is to put content and keywords on your website so that they can be found in search. The next step is to use the other delivery platforms of digital content, e-mail, social, and mobile, to deploy that content to the customer. The final topics in the book focus on the importance of data management and privacy. I discuss how to develop a database and to create an organization that puts data quality at its center. These practices are as critical to digital marketing success as the delivery platforms. Without quality data, no digital marketing program can be successful. After creating a database with high-quality data, I then briefly discuss the use of analytics in digital marketing. After reading this book, the reader should have a good idea of where to start on the path to an integrated digital marketing management strategy. Each chapter concludes with a list of action steps or "what to do next" to get started on implementing a digital marketing strategy as well as review questions and key terminology.